Synthesis and OER activity of NiO coatings with micelle–templated mesopore structure. Issue 3 (15th March 2016) - Bernicke, Michael; Eckhardt, Björn; Lippitz, Andreas; Ortel, Erik; Bernsmeier, Denis; Schmack, Roman; Kraehnert, Ralph
Abstract: Catalysts based on nickel oxide are some of the most active catalysts for the oxygen evolution reaction (OER) in alkaline media. However, preparing catalytic coatings with high surface area and good accessibility of the active sites remains challenging. We present a new approach for the synthesis of homogeneous and binder‐free nickel oxide coatings comprising a highly accessible ordered mesopore structure. The synthesis is achieved via evaporation induced self assembly utilizing PEO‐PB‐PEO triblock copolymers as pore template and a chemical complex of Ni 2+ and citric acid as precursor. Excessive crystallization behaviour of NiO is avoided by thermal conversion of the precursor into an amorphous Ni carbonate intermediate, followed by transition of the carbonate into the metal oxide. We present a comprehensive analysis of the obtained materials in terms of morphology, crystallinity, surface area, composition, and OER activity of differently calcined catalysts. Retaining a low crystallinity and high surface area during the synthesis proofs to be the most important factor in obtaining a highly active OER catalyst. Abstract : Nickel oxide catalysts are some of the most active compounds for alkaline oxygen evolution reaction (OER). We present a new approach for the synthesis of nickel oxide coatings with high surface area and ordered mesopore structure via evaporation induced self assembly utilizing PEO‐PB‐PEO and a chemical complex of Ni 2+ and citric acid. We present a comprehensive analysis of the materials in terms of morphology, crystallinity, surface area, composition, and OER activity of differently calcined catalysts.